STRATEGI KEBIJAKAN PEMERINTAH KABUPATEN PAMEKASAN TENTANG EKONOMI KERAKYATAN MELALUI PEMBERDAYAAN DAN PENGUATAN MANAGEMEN PERMODALAN KOPERASI BERBASIS SYARIAH DI DESA CEGUK - Handayani, Sri; Hidayat, Ainur Rahman (STAIN PAMEKASAN, 2016)
This is an economic study specifying in Sharia Cooperation as the process of empowerment to increase the economy of kerakyatan (public based economy). The focuses of study are firstly: how is the mapping of local potencies as the basic capital of the establishment of Sharia cooperation in Ceguk Village? Secondly, how is the acceleration of manager quality skill of the sharia cooperation in fulfilling the members need? Thirdly, how are the social networks created to upgrade the cooperation so that it becomes autonomous. Fourthly, how to manage, strengthen, and develop sharia cooperation in increasing managerial aspects? The data analysis techniques used by this research are: firstly, the mapping of local potencies; secondly, the upgrading of the manager skills; thirdly, strengthening the social networks among the mangers and stakeholders; fourthly, application of administration of managerial aspects, the process of accompaniment, and the formulation of the AD/ART (basic articles of understandings) of sharia cooperation. The results of research indicate that firstly, the chair of KJKS Al Ijtihad stated that the members are unable to settle up the debts however it creates the dependency of farmers to the middlemen. The culture of entrepreneurship of the farmers are remain simple it is characterized with the model of family management that the orientation tends to be more consumptive based rather than saving based particularly in the period of famine. Secondly, the researchers have accompanied the activity of manual finance note. The outcome of the audit shows that expenses on the basis of software on May 2015 were stated Rp. 20.000. However, it was different after the crosschecked was done, the expense was much greater, it was Rp. 36.000. It resulted inaccurate the finance report. The inaccuracy affected invalidity that the finance report cannot be used as control and planning device for the cooperation or investors for investment; thirdly, the strengthen of social networks among, sharia cooperation, stake holders, Dinas Koperasi (state cooperation service) and UMKM through FGD (Focus Group Discussion). The cooperation among these stakeholders is built on the basis of solid rooted trust in society; fourthly, management, strengthening, and development of KJKS Al Ijtihad have been focused on the application of the administration of managerial aspects, process of accompaniment, post training practice, and the formulation of AD/ART (basic articles of understandings) with monitoring and evaluation.